Alfabetização em saúde de cuidadores informais de idosos com Alzheimer - Cunha, Jamille Pinheiro (2017)
Alzheimer's brings on loss of autonomy and independence in the elderly, causing it to need direct assistance from caregivers. In the family context, the informal caregiver needs to seek, understand and share information about elder care. It is believed that the higher Health Literacy of the caregiver on care for the elderly with Alzheimer's, the better the quality of life of this. The aim is to evaluate the Health Literacy of informal caregivers of elderly people with Alzheimer's disease. Instant study, qualitative approach, was carried out with 42 informal caregivers of elderly people with Alzheimer's in the Ambulatory of the Centre for Elderly Care in Fortaleza. Caregivers were selected intentionally and for convenience. Inclusion criteria were: being an informal caregiver of the elderly with Alzheimer's and enrolled in the outpatient clinic; be the primary responsible for the care; be accompanying the elderly person in some care. The sociodemographic questionnaire of the caregiver and elderly care and the Health Literacy instrument were used for data collection. The analysis was done through the Statistical Package for Social Sciences program version 20.0 of the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires version 0.6 and the qualitative content analysis proposed by Mayring. The levels of Health Literacy were analysed taking as reference to the World Health Organization classification. The research was approved by the Research Ethics Committee from the Federal University of Ceará, under the number of opinion 1,457,063. The caregivers were mostly women with work overload, lack of knowledge and no support social support. Regarding the classification of Literacy in Health, there was a prevalence of functional and conceptual levels. Caregivers sought information about elderly care in the health services. Regarding the understanding of the information received, although they report understanding, some caregivers remained in doubt. The family was the main means of sharing the information received by caregivers. Participation in a support group was a resource that was favourable to the caregiver. From this perspective, it is necessary for the nurse to provide support to the informal caregiver of the elderly with Alzheimer's, encouraging them to participate in the support group, educational meetings and training courses for the caregiver offered by the service.